ATTITUDES TOWARD VOLUNTARY CHILDLESSNESS VERSI BAHASA INDONESIA: ADAPTASI ALAT UKUR - Fauziah Taslim; Rahmah Rezki Elvika; Aufizzahra As Syafiyah; Agitia Kurniati Asrila (Universitas Negeri Padang, 2025)
The adaptation of the Attitudes Toward Voluntary Childlessness Scale is a useful measurement tool for assessing aspects related to being childfree, such as families who do not wish to have children, the necessity of children for a family to be happy/meaningful, and whether society supports individuals' choices not to have children. The adaptation of the Attitudes Toward Voluntary Childlessness Scale is essential because there is no suitable measurement tool in Indonesian to accurately measure the concept of being childfree, especially in the context of families who choose not to have children. This measurement tool consists of 24 items and has undergone six stages of adaptation following cross-cultural adaptation guidelines. Through testing on 50 adults in Indonesia, a reliability coefficient of 0.906 was obtained to measure indicators related to individuals who do not have children, the necessity of children for a family to be happy/meaningful, and whether society supports individuals' choices not to have children. Therefore, the adapted Attitudes Toward Voluntary Childlessness Scale can be used in future research to predict various variables related to the concept of being childfree in Indonesia.